Sejarah Lembaga Pendidikan Islam di Indonesia sebelum Kemerdekaan (Abad 7 dan 8 Masehi) - Iskandar (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
The history of Islam inscribed on the archipelago is actually inseparable from the development of Islamic education in Indonesia. To be precise, the development of Islamic education has an age that is almost the same as the history of Islamic travel in Indonesia. The history of Islamic education is as old as the entry of Islam into Indonesia. This is because the followers of Islam who were still relatively new at that time, will certainly learn and understand about the teachings of Islam. Even though in a simple sense, the learning process that time had happened. From here, Islamic education began to emerge. Where at frst they studied in homes, langgar/surau, mosques and later developed into boarding schools. The development of Islam in the Arabian Peninsula in the 7th century has implications for the spread of Islam to various parts of the world with several channels of the Islamization process in Indonesia, namely, trade, marriage, art, and education.